Crystal growth of cyclodextrin‐based metal‐organic framework with inclusion of ferulic acid. Issue 7 (17th June 2015) - Michida, Wataru; Ezaki, Masato; Sakuragi, Mina; Guan, Guoqing; Kusakabe, Katsuki
<x xml:space="preserve">Abstract</x> Metal‐organic frameworks (MOFs) are porous materials consisting of infinite networks of metal ions or clusters bridged by organic ligand through metal‐ligand coordination bonds. Cyclodextrin‐based MOF (CD‐MOF) was found to be formed at room temperature in highly basic solution (pH>13.0) using γ‐cyclodexterin and potassium hydroxide. The crystallization of CD‐MOF with inclusion of ferulic acid was possible even at pH 6.8.